Estimation of the volume of icebergs calved from the outlet glaciers of the Severnaya Zemlya archipelago for 2014–2019 - I. A. Bychkova; V. G. Smirnov (Лëд и снег, 2021)
Volume of icebergs calved from the output glaciers located on the Northern Land during 2014–2019 was estimated using the satellite information. High-resolution satellite data were obtained in the visible spectral range from the non-commercial satellites Sentinel‑2 (spatial resolution 10 m) and Landsat‑8 (spatial resolution 15 m). Data collection was carried out under conditions when the natural illumination in the Arctic was sufficient (March–September) to make pictures in the visible spectral range. About 100 satellite images were analyzed for each year of the above period. The technique used for the iceberg detection is based on statistical criteria for finding the gradient zones in the analysis of two-dimensional fields of satellite images. The generation of the iceberg from a particular glacier was verified by using a form template of the detected iceberg taking into consideration the following parameters of the object: the geometrical shape, dimensions, specific features of «picture» of the ice surface (presence and orientation of cracks, peaks, and lakelets of melt water). The iceberg height was determined by its shadow on the image. The calculated total annual volume of icebergs from the outlet glaciers was estimated 1.52–1.9 km3. According to satellite data, the annual area reduction of the Northern Land outlet glaciers averaged 13 km2. The greatest contribution is made by 12 outlet glaciers located on the Komsomolets and the October Revolution islands. Of these, six are from the Academy of Sciences ice dome, four – the glaciers of the Matusevich Fjord, the Vavilov Glacier and the Rusanov dome glacier № 12. Icebergs of maximum height (30–40 m) are produced by glaciers of the North-Eastern slope of the Academy of Sciences ice dome and glacier № 12 of the Rusanov dome. In general, according to satellite data of recent years, generation of icebergs from the outlet glaciers of the Northern Land shows a steady growth trend.